The Legal Strength of the Deed of Power to Sell as the Basis for Transfer of Land Rights - Taufik Hidayat Lubis; Rahmat Ramadhani (International Journal Reglement & Society (IJRS), 2021)
In practice, the granting of a power of attorney to sell as above has caused the power to sell to be used as the basis for the process of making an AJB behind the name and at the same time being used as a registration tool for the transfer of land rights at the Land Office where the land is located. Meanwhile, the power of attorney to sell is accompanied by a statement from a notary that explains that the deed of power of attorney to sell is not an absolute power of attorney prohibited by law or that land and buildings as objects in the deed of power of attorney to sell have been paid in full. The procedure used to collect data in this study is in the form of documentation, namely the guidelines used in the form of notes or quotes, searching for legal literature, books and others related to the identification of problems in this study both offline and online. Analysis of legal materials is carried out using the content analysis method which is carried out by describing the material of legal events or legal products in detail in order to facilitate interpretation in the discussion. The granting of power of attorney is specifically regulated in Chapter XVI, book III of the Civil Code where Article 1792 states: "The grant of power of attorney is an agreement that contains the granting of power to another person who accepts it to carry out something on behalf of the person giving the power of attorney". Furthermore, Article 1793 of the Civil Code states: "Power can be given and received by a general deed, by a letter under the hand even by a letter or by word of mouth. The acceptance of a power of attorney can also occur secretly and is concluded from the exercise of that power by the authorized person. The process of transferring land rights based on the Selling Power of Attorney has a strong legal basis because there are no legal rules that are violated as argued and proven above. So it is correct to say that the Deed of Authorization to Sell has transitional power as well as in the process of transferring land rights through the Deed of Sale and Purchase, as long as no rules are violated in the transition process. The legal protection provided by PPJB is paid off and the power to sell to the buyer if the seller dies is very strong and perfect because of the evidentiary nature of PPJB and the power to sell made before a public official in this case a notary. This is a form of guarantee of legal certainty and as a form of legal protection for buyers who have paid the full price they have paid but have not been able to make AJB and reverse registration because one way or another there are conditions that have not been fulfilled